PERAN TINGKAT UPAH DALAM MENDORONG PERTUMBUHAN MIGRASI MASUK DI PULAU SUMATERA - Deki Fujiansyah; Andri Irawan (Ekonomika, 2026)
The aim of this study is to analyze the partial effect of wage levels on the growth of in-migration in Sumatra Island during the period of 2018–2022. This research employs a quantitative approach using secondary data obtained from the Central Bureau of Statistics (BPS) covering provinces in Sumatra Island. The dataset consists of time-series data for five years (2018–2022) and cross-sectional data from ten provinces in Sumatra. The method used in this study is panel data regression analysis, and the data were processed using E-Views software. The independent variable in this study is wage level (X), while the dependent variable is the growth of in-migration (Y). The results indicate that wage level (X) has a positive and significant effect on the growth of in-migration (Y) in Sumatra Island during the period of 2018–2022. The coefficient of determination shows that wage level (X) explains 33.00% of the variation in the growth of in-migration in Sumatra Island, while the remaining 67.00% is explained by other factors not included in the model of this study.